Home song - Spencer, LaVyrle (New York : Jove Books, 1994)
A perfect marriage begins to disintegrate when a single mother arrives in town, son in tow. She enrolls him in a school where the couple teach, which is how the husband learns he has a second son, the fruit of a one-night stand on the eve of his marriage. To make matters worse, the boy starts dating the couple's daughter. Hard to keep a secret under such circumstances. By the author of Family Blessings.
Keywords: High school principals -- Fiction; Minnesota -- Fiction; Domestic fiction